2022
DOI: 10.2147/ijwh.s379128
|View full text |Cite
|
Sign up to set email alerts
|

Struma Ovarii Associated with Ascites and Elevated CA125: Two Case Reports and Review of the Literature

Abstract: Struma ovarii is a rare variety of specialized monodermal mature ovarian teratoma, it is composed predominantly of thyroid tissue. Ascites is present in one third of patients. The combination of struma ovarii, marked ascites and elevated CA125 is a rare condition, which may mimic ovarian cancer. We described two cases presenting with pelvic mass, ascites and elevated serum CA125 levels, frozen section and final pathology turned out to be struma ovarii. Ascites disappeared and the level of CA125 returned to nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The combination of struma ovarii with ascites and pleural effusion simultaneously, first described by Meigs in 1954 and commonly referred to as the pseudo-Meigs syndrome is a rare occurrence. 3,4 Ascites is believed to be mainly transudate from the tumor surface, which exceeds the absorptive capacity of peritoneum or obstructs lymphatics due to tumor cells or increases the permeability of the neovasculature with protein leakage and an inflammatory reaction. [3][4][5] Despite the predominance of thyroid tissue, hyperthyroidism is present only in 5% to 10% of struma ovarii cases, with antibodies produced by the neoplastic thyroid follicles for the TSH receptor being the putative cause.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of struma ovarii with ascites and pleural effusion simultaneously, first described by Meigs in 1954 and commonly referred to as the pseudo-Meigs syndrome is a rare occurrence. 3,4 Ascites is believed to be mainly transudate from the tumor surface, which exceeds the absorptive capacity of peritoneum or obstructs lymphatics due to tumor cells or increases the permeability of the neovasculature with protein leakage and an inflammatory reaction. [3][4][5] Despite the predominance of thyroid tissue, hyperthyroidism is present only in 5% to 10% of struma ovarii cases, with antibodies produced by the neoplastic thyroid follicles for the TSH receptor being the putative cause.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Ascites is believed to be mainly transudate from the tumor surface, which exceeds the absorptive capacity of peritoneum or obstructs lymphatics due to tumor cells or increases the permeability of the neovasculature with protein leakage and an inflammatory reaction. [3][4][5] Despite the predominance of thyroid tissue, hyperthyroidism is present only in 5% to 10% of struma ovarii cases, with antibodies produced by the neoplastic thyroid follicles for the TSH receptor being the putative cause. 6 Elevation of serum CA125 (ranging from 124.9 to more than 5218 IU/L in different reports) is an intriguing finding in struma ovarii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike common ovarian teratomas, neither ultrasonography nor CT, or MRI showed satisfactory efficacy in the identification of SO with or without serum tumor markers [ 4 , 19 21 ]. Besides, some patients with SO presented elevated CA125 levels and/or remarkable ascites that highly suspected epithelial ovarian carcinoma (EOC) [ 3 , 21 ]. Our study showed that one-fifth of the patients were suspected of malignancy either in the SO subgroup or the overall population, and even metastasis at initial presentation could be observed in the SO subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Struma ovarii (SO) is a monodermal teratoma, characterized by the presence of more than 50% of thyroid tissue, which accounts for about 5% of ovarian teratomas and less than 1% of all ovarian tumors [ 1 , 2 ]. Its clinical manifestations include asymptomatic ovarian mass, abdominal discomfort, thyrotoxicosis, ascites, elevated CA125, or even metastasis, presenting unpredictable biological behaviors with overlapping benign and malignant features [ 3 5 ]. Malignant transformation of SO to an ovarian strumal carcinoid (OSC) or malignant struma ovarii (MSO) is also reported in rare circumstances [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%